Is dry needling an effective treatment for tennis elbow? A literature review - Grabowski, Filip; Rulewska, Natalia; Neska, Dagmara; Siemko, Jakub; Chodkowski, Jakub; Prystacka-Szar, Dominika; Stadler-Szajda, Justyna; Czyżnikiewicz, Adrianna; Stołowski, Wenancjusz; Bujak, Magdalena; et al. (Quality in Sport, 2025)
Introduction:Tennis elbow, or lateral epicondylitis, affects around 1% to 3% of the population, causing pain and functional limitations, yet its exact causes and degenerative mechanisms are still not fully understood. Research indicates that tendinopathy primarily arises from new blood vessel formation and collagen fiber disruptions, while tennis elbow complicates diagnosis and treatment due to a mix of biomechanics, occupational factors, and individual variations. Despite various treatments available for tennis elbow, no single option is universally recognized as superior, with the primary recommendation being to rest from activities that worsen the condition. To alleviate pain after exercising, options include applying ice, using oral or topical NSAIDs, or exploring corticosteroid therapy, with more invasive treatments like dry needling being effective for managing myofascial pain and trigger points when basic methods fall short. Aim: The aim of this article is to explore the underlying mechanisms of tennis elbow and assess the effectiveness of treating it through dry needling. Review methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was undertaken using the searchterms encompassing the following keywords: tennis elbow, lateral epicondylitis, dry needling, tennis elbow pathophysiology. Conclusion: Dry needling has shown success in relieving symptoms of chronic lateral epicondylosis that haven’t improved with standard therapies. This method is safe, cost-effective, and can be carried out by practitioners skilled in upper extremity anatomy and rehabilitation, but further extensive research with larger sample sizes, randomization, and control groups is needed to more accurately assess the effectiveness of dry needling for treating tendinopathies.